2020
DOI: 10.3390/su12072752
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Local Climate Zone Cooling Achieved through Modification of Trees, Albedo and Green Roofs—A Case Study of Changsha, China

Abstract: By exploring the cooling potential of tree quantity, ground albedo, green roofs and their combinations in local climate zone (LCZ)-4, LCZ-5, and LCZ-6, this study focuses on the optimum cooling level that can be achieved in open residential regions in Changsha. It designs and models 39 scenarios by integrating in situ measurement and ENVI-met numerical simulation and further compares cooling effects of various combinations of the cooling factors. The results show that (1) an increased number of trees and highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…In all future scenarios, but especially in TBS and MTC, taller buildings (predominantly mixed use, and with a larger footprint) underperformed in terms of tree-based reductions in total SRA and BCED. This observation is supported by other modelling research noting lower cooling effects in areas with tall buildings despite increasing trees (by 30% or 60%; Chen et al 2020). The lower tree shading impact for these taller/larger buildings in TBS and MTC can also be attributed to the generally smaller tree sizes associated with the climate-adapted species used.…”
Section: Research Implicationssupporting
confidence: 74%
“…In all future scenarios, but especially in TBS and MTC, taller buildings (predominantly mixed use, and with a larger footprint) underperformed in terms of tree-based reductions in total SRA and BCED. This observation is supported by other modelling research noting lower cooling effects in areas with tall buildings despite increasing trees (by 30% or 60%; Chen et al 2020). The lower tree shading impact for these taller/larger buildings in TBS and MTC can also be attributed to the generally smaller tree sizes associated with the climate-adapted species used.…”
Section: Research Implicationssupporting
confidence: 74%
“…Urban nature has been widely recognized as an important part of urban infrastructure providing a variety of ecosystem functionalities and services, contributing to sustainable urban development [5]. Findings of empirical investigations have indicated that the presence of natural areas and green infrastructures in cities has the potential to fend off the adverse challenges on vulnerable urban environments and positively affects the life quality of inhabitants [6][7][8][9][10][11]. Consequently, investigations on people's comfort perception related to urban nature and green infrastructure grows steadily [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 168 datapoints Surface parameter extraction from satellite images LST patterns have been linked with air temperature by various researchers (Anbari et al, 2019;Hooker et al, 2018;Unger et al, 2009). Few studies have elaborated the effects of albedo properties and vegetation cover on heat retention and dissipation (Akbari et al, 2001;Chen et al, 2020). Based on such previous observations, four parameters were selected as independent variables to model maximum T a .…”
Section: Dataset Descriptionmentioning
confidence: 99%